Training matters - "Rainbird, Helen" (Oxford, 1990)
This book is an analysis of the ways in which unions can and should organize training issues. Lack of training at all levels in British industry has been, and remains, a significant threat to its international competitiveness. In the 25 years since the Industrial Training Act, policy making in this field has undergone turbulent change. Over the last decade government has pushed responsibility back into the hands of employers, forcing unions to the sidelines of the policy making process. This book covers initial training, retraining, the effects of new technology, flexible working practices, labour market deregulation and the wider policy issues. It is an important restatement of union activity and commitment in the training field and includes the latest empirical research on nine major unions. This is an examination of the field based on a comprehensive research programme in conjunction with 9 major unions on training issues, covering training in the light of new technology, flexible workforces and the new realism.
Keywords: Economics